(untitled) (Chemical Engineering Research Bulletin, 2013)
A comparison was studied for non-treated and pretreated corn stover with dilute alkaline peroxide and dilute acid treatment respectively for bioethanol production by simultaneous saccharification and fermentation (SSF) process in a continuous stirred batch bioreactor using fungi Aspergillus oryzae. The optimum parameters for bioethanol fermentation were: time, 48 h; pH, 6.0; temperature, 50ºC; stirring speed, 35 rpm; and corn stover loading, 35 g/L. The maximum concentration of bioethanol at optimum fermentation process parameters were 0.762 g/g, 0.799 g/g and 0.819 g/g for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. Maximum yields of bioethanol were 0.399 g/L h, 0.420 g/L.h and 0.431 g/L h of corn stover at optimum parameters for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. The sp. growth rate (m) were 5.30 s?1 , 5.54 s?1, and 5.93 s?1 and maximum sp. growth rate (m max) were 10.60 s?1 , 11.08 s?1 and 11.86 s?1 using Monod model for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. The Monod parameter (Ks) were 33.87 g/L, 34.21 g/L and 34.85 g/L for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. The sp. enzyme activity (?) were 1192 min?1, 1463 min?1 and 1559 min?1 and maximum sp. growth rate (? max) were 2384 min?1, 2926 min?1 and 3118 min?1 using Michaelis-Menten enzyme kinetic model for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. The Michaelis-Menten parameter (Km) were 34.42 g/L, 34.63 g/L and 34.85 g/L for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover respectively. The first order rate constants (k) were 0.014 h?1 , 0.016 h?1 and 0.019 h?1 for non-treated, dilute acid and dilute alkaline peroxide pretreated corn stover for continuous stirred batch bioreactor respectively. DOI: http://dx.doi.org/10.3329/cerb.v16i1.6659 Chemical Engineering Research Bulletin 16(2013) 33-44